Tratamento inseticida para controle de pragas do armazenamento e a qualidade fisiológica de sementes de trigo - Ferreira, Cairo Cezar (2012)
The pest-insects of storage are limiters the conservation of wheat seeds, because damage the product or invalidate their use, causing qualitative and quantitative losses. The seeds require the use of preventive measures if they are not infested and curatives when infested by pest-insects to ensure the preservation of physiological and sanitary quality during storage. In order to determine the effect of insecticide treatment on the physiological quality of wheat seeds during storage, were segregated four lots, BRS 210. Treatments consisted: a) control without insecticide application b) expurgation with phosphine at a dose of 2.0 g i.a/m3; c) liquid chemical treatment, using Pirimiphos-methyl to 6 g i.a/t (12 mL Actellic of 500 EC/t) Bifenthrin 0.4 g i.a/t (16 ml ProStore 25 EC / t); d) inert powder using diatomaceous earth to 860 gy/t (Keepdry to 1000 g/t). Expurgation was monitored by concentration of phosphine using the concentration meter Silo Chek. Fortnightly, was monitored the presence of pests-insects in stored seeds. Monthly, were conducted in laboratory germination test, emergence in sand at greenhouse and laboratory accelerated aging. The treatments with insecticides were effective in the prevention and control of pest-insects in seeds. The monitoring of phosphine gas during expurgation demonstrated the maintenance of minimum concentration required to supress life stages of the pest-insects. The chemical insecticides and diatomaceous earth did not allow the development of pest-insects and insecticide treatments did not affect the physiological quality of wheat seeds during storage.